2012
DOI: 10.1177/1040638712456976
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance evaluation of calf diarrhea pathogen nucleic acid purification and detection workflow

Abstract: Calf diarrhea (scours) is a primary cause of illness and death in young calves. Significant economic losses associated with this disease include morbidity, mortality, and direct cost of treatment. Multiple pathogens are responsible for infectious diarrhea, including, but not limited to, Bovine coronavirus (BCV), bovine Rotavirus A (BRV), and Cryptosporidium spp. Identification and isolation of carrier calves are essential for disease management. Texas Veterinary Medical Diagnostic Laboratory current methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…Primer and probe sequences for detection of BTV, EHDV, and XIPC were adopted from previous publications. 14,16,31 The synthetic construct clone NISTag38 external RNA control sequence (GenBank accession no. DQ883679) is a unique artificial antigenomic sequence with no significant homology to annotated species sequences.…”
Section: Tvmdl Workflowmentioning
confidence: 99%
“…Primer and probe sequences for detection of BTV, EHDV, and XIPC were adopted from previous publications. 14,16,31 The synthetic construct clone NISTag38 external RNA control sequence (GenBank accession no. DQ883679) is a unique artificial antigenomic sequence with no significant homology to annotated species sequences.…”
Section: Tvmdl Workflowmentioning
confidence: 99%
“…Primer and TaqMan probe sequences for detection of ASFV, CSFV, FMDV, and XIPC were taken from previous publications, 1,4,20,21 and optimal oligonucleotide concentrations were determined through empirical testing. Fluorescence and/or quencher molecules for oligonucleotide probes for ASFV and FMDV were modified from their original USDA designs in order to make the mRTqPCR compatible for simultaneous discrimination of 4 different targets.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…As early as in 1972, Stair et al [2] reported pneumoenteritis in calves induced by coronaviruses. The first isolation of BоCV from bronchial secretion and nasopharyngeal washings of calves with signs of pneumonia occurred in 1982 and later, it was determined as bovine respiratory coronavirus (BRCoV) [1,2] . Strains isolated from diarrhoeic newborn calves and cattle have been classified as enteric or enteropathogenic coronaviruses (BECoV) [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Bоvine Corona Virus -BoCV is outlined as one of primary etiological agents causing gastrointestinal diseases in newborn calves (calf diarrhoea -CD), winter dysentery (WD) in adult cattle and respiratory infections in calves and cattle in fattening farms -pneumoenteritis syndrome [1] . As early as in 1972, Stair et al [2] reported pneumoenteritis in calves induced by coronaviruses.…”
Section: Introductionmentioning
confidence: 99%